The Effect of Raw Material Inventory Management On Work Productivity of PT. Kss (Karunia Sejahtera Sejati) Nias Branch - Halawa, Alfonsus; Gea, Jeliswan Berkat Iman Jaya; Mendrofa, Martha Surya Dinata; Zebua, Serniati (Economics and Business Journal (ECBIS), 2025)
This study aims to determine the Effect of Raw Material Inventory Management on Work Productivity of PT. KSS (Karunia Sejahtera Sejati) Nias Branch. The research method used is a quantitative approach. The sample in this study amounted to 31 respondents. Data collection techniques were carried out through the distribution of questionnaires and documentation. Data analysis techniques used simple linear regression analysis, classical assumption tests, coefficient of determination tests and t-tests with the help of the SPSS version 25 statistical application. The R2 Determination Test that has been carried out obtained the result that the R2 value is 0.620. This shows that the Raw Material Inventory Management variable (X) can explain Work Productivity (Y) by 62%, while the remaining 38% is explained by other factors not covered in this study. Based on the data analysis, it shows that simultaneously the Raw Material Inventory Management variable has a positive and significant effect on Work Productivity with a significance of 0.000 <0.05 and the T-value obtained is 6.877> 1.696 so that it can be concluded that Ha is accepted and has an effect on the dependent variable of Work Productivity (Y). The conclusion of this study is that the Raw Material Inventory Management variable partially or simultaneously has an effect on Work Productivity and it is recommended that PT. KSS (Karunia Sejahtera Sejati) provide increased competency and understanding of employees regarding inventory management that is very necessary so that they are able to carry out their tasks more efficiently and effectively, so that work productivity increases. Periodic training and socialization regarding inventory management and its relationship to work productivity must continue to be carried out.